Giant Mucometrocolpos in Newborn Girl - I.P. Zhurilo; V.P. Perunsky; T.I. Ivaschenko; R.F. Abdulin; G.N. Turpakova (Zaslavsky O.Yu., 2012)
The article describes a rare case of a giant mucometrocolpos in newborn girl. Cystic formation was first detected in utero by ultrasound control in 34 weeks of pregnancy. The final diagnosis was made during surgery. From the dilated vagina and uterus there were evacuated up to 350 cm3 of mucous content. Resection of the wall of cystic formation, dissection of vaginal membrane and external drainage of the cavity had been carried out. Histological examination revealed degenerative changes in the epithelium and glandular apparatus of the vaginal wall. Recovery.